Writing Errors in Students’ Foreign Language Acquisition - Siti Sumarti; Pratomo Widodo (Makassar State University, 2020)
Lewis gives some type of writing errors. Those type of errors are omission, overuse, meaning, and errors related to forms. The aim of this study is to explain kinds of writing errors, as proposed by Lewis, occurs in language acquisition of English language in elementary school level. In this research researcher mainly used the qualitative research design in the strategy of descriptive. The subject in this research is writing errors. Meanwhile, the data or object is written language related to English language which is taken from elementary students note in English subject. The students are vary from grade four to grade six. The method and technique in collecting data is metode simak or by reading attentively specifically in noting technique and the technique for analyzing data is metode agih or distributional method. Research instrument is human instrument. Based on the findings, the kinds of errors which occurs in students writing are omission type of writing errors, overuse type of writing errors, meaning type of writing errors, and related forms type of writing errors. The writing errors that mostly occurred is related forms of writing errors. In the findings, the related forms writing error which found is specifically in pronunciation and spelling.